If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12.5x+30=(-7.5x)+90.5
We move all terms to the left:
12.5x+30-((-7.5x)+90.5)=0
We calculate terms in parentheses: -((-7.5x)+90.5), so:We get rid of parentheses
(-7.5x)+90.5
We get rid of parentheses
-7.5x+90.5
Back to the equation:
-(-7.5x+90.5)
12.5x+7.5x-90.5+30=0
We add all the numbers together, and all the variables
20x-60.5=0
We move all terms containing x to the left, all other terms to the right
20x=60.5
x=60.5/20
x=3+0.5/20
| -8x-2=5x+7 | | 3(b+2)-4(b-3)=5b | | 4x-2(1-x)=-32 | | -3(15g-5)=5(-12-12g) | | 2x+3=9*5 | | -2(v+6)+6v=4 | | 2x+0.5x=430000 | | 3a-8=118 | | 2.5x-1.4=6.1 | | -2x+7=5-4x+1 | | 4r+9=77 | | 5(n+1)=7(n-3) | | 4(x-6)+2x=-24+6x | | 53x−4+23x+10=9 | | (3x+7)+(9x-43)=189 | | y^2-((y^2)/4)-(4/(y^2))-2=0 | | 8x+5=5-2x | | -3=v-10 | | -2(3x+9)=2(-3x+9) | | 2+v/2=5 | | 16x=1/64x= | | f(7)=26 | | 2r+5/3+6=19 | | 10x-14-12x+3=-23 | | -7x-8=5x+8(8x-1) | | -2(x+3)=x-9+3(4x+3) | | 3x-10=9x+12 | | f(7)=27 | | -6(12b-14)+18b=-12b | | y^2-(y^2/4)-(4/y^2)-2=0 | | |x-3|-10=4 | | 7b/6+3b/2=2b/3+18 |